Current Account and Real Exchange Rate Dynamics in Indonesia - Mochtar, Firman; Affandi, Yoga (Economics and Finance in Indonesia, 2015)
We analyze the role of both permanent and temporary factors in affecting the Indonesian current accountÂ and real exchange dynamics before and after 2000. Adopting Lee and Chinn (1998; 2006) approach as well as Chinn et al. (2007), two results stand out. First, we confirm that the behavior of the real exchange rate has altered since 2000. Identifications show that permanent shocks are the primary causes for the movements of the real exchange rate after 2000, while in the period before 2000, the Indonesian real exchange rates changes are characterized by greater dominance of temporary shocks. The apparent change in the real exchange rate behavior may be strongly justified by the implementation of free-floating exchange rate systems since August 1997. Second, the shift of the real exchange rate behavior after 2000 does not necessarily affect the current account dynamics. Empirical evidence confirms that the variance of current account post 2000 remains largely due to temporary shocks. Albeit having increasing influence, permanent shocks have insignificant effect in explaining fluctuations of the current account. In this sense, the current account surplus after 2000 is attributed largely to nominal variables such as price increase, while the impact of productivity improvement is still limited.